GAMBARAN HEMOGLOBIN DAN INDEKS ERITROSIT PADA REMAJA PUTRI - Puspita, RR. Salsabila; Wowor, Mayer Ferdinand; Rambert, Glady Inri (Universitas Sam Ratulangi, 2025)
Background: Anemia is a global health issue affecting 24.3% of the world's population, with a high prevalence among women of reproductive age. In Indonesia, the prevalence of anemia in women is 27.2%, higher in rural areas. Adolescent girls are particularly vulnerable to anemia due to menstruation and inadequate nutritional intake, which can impact productivity, immunity, and pregnancy complications. Hemoglobin levels and erythrocyte indices (MCV,MCH, MCHC) are crucial for diagnosing and classifying anemia. Objective: To describe hemoglobin levels and erythrocyte indices among adolescent girls at SMA Kristen Sonder, Minahasa Regency. Method: This type of research uses a descriptive design. The sample consisted of 30 respondents selected using purposive sampling based on inclusion and exclusion criteria. Primary data were obtained through complete blood count tests and questionnaires. Results: Most samples had normal hemoglobin levels (90%), while 10% had low hemoglobin levels. Erythrocyte indices showed normal MCV in 86.6% of samples and low in 13.3%; normal MCH in 80% and low in 20%; and normal MCHC in 100% of samples. Of the three samples with anemia, two were microcytic, one was normocytic, and none were macrocytic. Conclusion: The majority of adolescent girls at SMA Kristen Sonder, Minahasa Regency, had normal hemoglobin levels and erythrocyte indices. Keywords: Adolescent girls; Erythrocyte indice; Hemoglobin